Pharmacological mechanisms of traditional Chinese medicine in treating gastric cancer: a focus on the ferroptosis regulation - Gao, Shanshan; Wang, Huijuan (Frontiers in Pharmacology, 2026)
IntroductionIn recent years, the incidence and mortality rates of gastric cancer (GC) have continued to rise, making it a major public health concern that poses a severe threat to human health. Although significant progress has been made in the treatment of GC in recent years, the overall median survival time for patients remains short. This situation is primarily attributed to the high metastatic potential and recurrence rate of tumors, as well as the generally low sensitivity of patients to radiotherapy and chemotherapy. Therefore, the development of safe, effective, and sustainable therapeutic strategies has become an urgent and critical issue in global medical research. Chinese herbal medicine, with its unique advantages such as low cost, minimal risk of drug resistance, and fewer adverse effects, has accumulated extensive clinical experience in the treatment of GC, demonstrating broad application prospects.MethodsWe systematically searched databases including PubMed, Web of Science, Scopus, and ISI using the following keywords: “gastric cancer/tumor,” “natural products,” “natural extracts,” “traditional Chinese medicine extracts,” “traditional Chinese medicine formulas,” and “ferroptosis.” A comprehensive review and analysis of the existing relevant literature were conducted.ResultsCurrently, the management of gastric cancer (GC) primarily relies on surgical resection, complemented by a range of therapeutic modalities including radiotherapy, chemotherapy, targeted therapy, and immunotherapy. However, the overall median survival rate for patients with GC remains unsatisfactory. In recent years, accumulating evidence has indicated that Chinese herbal medicine may play a significant role in the treatment of GC through the regulation of ferroptosis. Emerging studies have further demonstrated that Chinese herbal medicine not only induces ferroptosis in tumor cells and suppresses tumor proliferation but also enhances the therapeutic efficacy of radiotherapy, targeted therapy, and immunotherapy, thereby improving overall treatment outcomes. This article reviews recent advances in research on Chinese herbal medicine-mediated modulation of ferroptosis in GC and discusses the potential molecular mechanisms underlying ferroptosis in this malignancy, aiming to provide a theoretical foundation for the development of precise diagnostic approaches and targeted therapeutic strategies.ConclusionStudies indicate that Chinese herbal medicines targeting ferroptosis hold promising potential in GC therapy, not only laying a theoretical foundation for elucidating the pathogenesis of GC and establishing ferroptosis-targeted Chinese herbal medicine intervention strategies, but also opening new avenues for the clinical prevention and treatment of GC.